Irish Poetry in Faro de Vigo (1961-1981): Francisco Fernández del Riego and Álvaro Cunqueiro in the Galician Newspaper - Jarazo Álvarez, Rubén (ABEI Journal, 2011)
Contemporary poetry, as we will try to demonstrate in this case study,has been essential for scholars and critics in favour of free speech and against cultural repression during Spanish Dictatorship. In this sense, professionals from peripheral regions such as Catalonia, Basque Country and Galicia were in favour of foreign texts and their reception in Spanish culture as an infallible method to reveal twentieth century Spanish culture from obscurantism. In this article we will focus on the reception of literary texts produced by significant Irish poets translated in the Spanish literary panorama, paying special attention to those translations and reviews produced by Álvaro Cunqueiro and Francisco del Riego.